Anisotropy and universality: The Oslo model, the rice pile experiment, and the quenched Edwards-Wilkinson equation - Pruessner,G; Jensen,HJ (PHYS REV LETT, 2003)
We show that any amount of anisotropy moves the Oslo model to another known universality class, the exponents of which can be derived exactly. This amounts to an exact solution of the quenched Edwards-Wilkinson equation with a drift term. We argue that anisotropy is likely to be experimentally relevant and may explain why consistent exponents have not been extracted in the rice pile experiments.